2019
DOI: 10.1002/ejhf.1693
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of pre‐discharge bio‐adrenomedullin as a marker of residual congestion and high risk of heart failure hospital readmission

Abstract: Plasma bio-ADM was measured in 1236 acute HF patients in the PROTECT trial at day 7 or discharge. Median discharge bio-ADM was 33.7 [21.5-61.5] pg/mL. Patients with higher discharge bio-ADM levels were hospitalised longer, had higher brain natriuretic peptide levels, and poorer diuretic response (all P < 0.001). Bio-ADM was the strongest predictor of discharge residual congestion (clinical congestion score > 3) (odds ratio 4.35, 95% confidence interval 3.37-5.62; P < 0.001). Oedema at discharge was one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 28 publications
3
55
0
1
Order By: Relevance
“…The preservation of endothelial integrity and influence on fluid balance might explain the important role of ADM in HF, where volume challenge, vascular leakage and formation of interstitial oedema are crucial. Recently, bio‐ADM level was shown to be a strong predictor of fluid overload in new‐onset or worsening HF, proposing bio‐ADM as a marker of congestion 10,26 . Besides its vasoactivity, 27 effects of ADM in the cardiovascular system include positive inotropy, inhibition of cardiomyocyte hypertrophy as well as natriuretic, angiogenic and anti‐inflammatory properties 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The preservation of endothelial integrity and influence on fluid balance might explain the important role of ADM in HF, where volume challenge, vascular leakage and formation of interstitial oedema are crucial. Recently, bio‐ADM level was shown to be a strong predictor of fluid overload in new‐onset or worsening HF, proposing bio‐ADM as a marker of congestion 10,26 . Besides its vasoactivity, 27 effects of ADM in the cardiovascular system include positive inotropy, inhibition of cardiomyocyte hypertrophy as well as natriuretic, angiogenic and anti‐inflammatory properties 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Bio‐adrenomedullin (bio‐ADM) is a possible marker of congestion . Pandhi et al . confirmed that high bio‐ADM levels at discharge are strongly associated with residual congestion in patients with acute HF.…”
Section: Acute Heart Failurementioning
confidence: 98%
“…confirmed that high bio‐ADM levels at discharge are strongly associated with residual congestion in patients with acute HF. Moreover, combined with high dose of loop diuretics, high bio‐ADM was associated with a four‐fold increased risk of HF rehospitalization at 60 days . Natriuretic peptides have a main role in the diagnosis and stratification of HF patients .…”
Section: Acute Heart Failurementioning
confidence: 99%
“…288 Mid-regional pro-adrenomedullin and bio-adrenomedullin provide a great accuracy in diagnosis of acute HF and detection of residual congestion. 289,290 Elevated levels of blood lactate, associated with hypoperfusion, and markers of multi-organ injury/dysfunction are predictors of poorer outcomes. [291][292][293] Worsening renal function is only associated with adverse events in patients without decreased BNP.…”
Section: Managementmentioning
confidence: 99%
“…Higher levels of mid‐regional pro‐adrenomedullin and its active form, bio‐adrenomedullin, were observed in the presence of volume overload and have been proposed as markers of congestion 288 . Mid‐regional pro‐adrenomedullin and bio‐adrenomedullin provide a great accuracy in diagnosis of acute HF and detection of residual congestion 289,290 . Elevated levels of blood lactate, associated with hypoperfusion, and markers of multi‐organ injury/dysfunction are predictors of poorer outcomes 291–293 .…”
Section: Acute Heart Failurementioning
confidence: 99%